OPTIMALISASI PERAN BADAN PERMUSYAWARATAN DESA TERHADAP PENGAWASAN PEMERINTAHAN DESA UNTUK MENCAPAI GOOD GOVERNMENT PASCA UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Maharani, Andina Elok Puri; Prehantoro, Fredyta (Res Publica: Jurnal Hukum Kebijakan Publik, 2017)
Badan Permusyawaratan Desa (BPD = The Villager Consultative Council) is democratic institution in a village. Since the law of Number 6 Of 2014 about village is applied, the position of The Villager Consultative Council has government function. The members of The Villager Consultative Council is representative of peoples of the village based on representation of the region which has been applied by the conference.From the result of the research and the discussion, a conclusion could be drawn that the role of The Villager Consultative Council in supervising government village to achieve good government exist in Pasal 55 and Pasal 73 The Law Number 6 of 2014 about village. That the role of Badan Permusyawaratan Desa is discussing and approving Rancangan Peraturan Desa with the Village Chief, accommodating and distributing peoples’ aspiration, supervising the Village Chief’s performance and forming Rancangan Anggaran Pendapatan dan Belanja Desa with the Village Chief.